Tele-nephrology in practice: Economic impact and primary care perspectives. - Sous, Sofia; Santos, Sofia; Braga, Beatriz; Cunha, Ana; Beirão, Idalina (Nefrología, 2026)
Aims Telemedicine used in nephrology has demonstrated non-inferiority to traditional care and acceptance by healthcare professionals and patients; however, cost effectiveness was less commonly reported. We aim to describe our centre's experience with virtual consultations (VCs) and estimate cost reduction, as well as assess general practitioners' (GPs) perspectives. Methods Retrospective study of the patients referred for VC between January 2020 and December 2022 at Unidade Local de Saúde de Santo António (ULSSA). We analyzed patients’ demographics, including distance to hospital and autonomy, and estimated economic savings related to nephrologist's time, patient transport and lost workdays. To assess GPs' perspective, we administered a brief, closed-question survey to GPs to assess awareness, use, and satisfaction with VCs. Results A total of 456 patients were included, of which 260 (57%) were female and median age was 80 years old (IQR 72-87). Distance from the hospital varied between one and 540 km, with a median distance of 16 km (IQR 6–19). Estimated total savings were €16,697.89, equivalent to €36.62 per patient per consult. The nephrologist time cost was estimated at €966.11 for virtual consultations compared with €3622.92 for initial face-to-face consultations, resulting in a time-related cost reduction of €2656.81. Forty-seven GPs of a total of 236 GPs (20%) completed the survey; from the responders, 28% had used VCs and 77% reported satisfaction with the response. Prescription guidance was the most identified strength of VC. Lack of awareness was the main barrier to use. Conclusions In this single-center experience, VCs reduced costs and travel burden while being acceptable to GPs. However, many GPs were unaware of this pathway, underscoring the need for promotion and integration in primary-care workflows. Future multicentre studies should evaluate clinical outcomes including avoidable face-to-face visits, hospitalizations, time to advice) and include patient and nephrologist perspective.